Fussing About Fission: Defining Variety Among Mainstream and Exotic Apicomplexan Cell Division Modes - Gubbels, Marc-Jan; Keroack, Caroline D.; Dangoudoubiyam, Sriveny; Worliczek, Hanna L.; Paul, Aditya S.; Bauwens, Ciara; Elsworth, Brendan; Engelberg, Klemens; Howe, Daniel K.; Coppens, Isabelle; Duraisingh, Manoj T. (Frontiers in Cellular and Infection Microbiology, 2020)
Cellular reproduction defines life, yet our textbook-level understanding of cell division is limited to a small number of model organisms centered around humans. The horizon on cell division variants is expanded here by advancing insights on the fascinating cell division modes found in the Apicomplexa, a key group of protozoan parasites. The Apicomplexa display remarkable variation in offspring number, whether karyokinesis follows each S/M-phase or not, and whether daughter cells bud in the cytoplasm or bud from the cortex. We find that the terminology used to describe the various manifestations of asexual apicomplexan cell division emphasizes either the number of offspring or site of budding, which are not directly comparable features and has led to confusion in the literature. Division modes have been primarily studied in two human pathogenic Apicomplexa, malaria-causing Plasmodium spp. and Toxoplasma gondii, a major cause of opportunistic infections. Plasmodium spp. divide asexually by schizogony, producing multiple daughters per division round through a cortical budding process, though at several life-cycle nuclear amplifications are not followed by karyokinesis. T. gondii divides by endodyogeny producing two internally budding daughters per division round. Here we add to this diversity in replication mechanisms by considering the cattle parasite Babesia bigemina and the pig parasite Cystoisospora suis. B. bigemina produces two daughters per division round by a ‘binary fission’ mechanism whereas C. suis produces daughters through both endodyogeny and multiple internal budding known as endopolygeny. In addition, we provide new data from the causative agent of equine protozoal myeloencephalitis (EPM), Sarcocystis neurona, which also undergoes endopolygeny but differs from C. suis by maintaining a single multiploid nucleus. Overall, we operationally define two principally different division modes: internal budding found in cyst-forming Coccidia (comprising endodyogeny and two forms of endopolygeny) and external budding found in the other parasites studied (comprising the two forms of schizogony, binary fission and multiple fission). Progressive insights into the principles defining the molecular and cellular requirements for internal versus external budding, as well as variations encountered in sexual stages are discussed. The evolutionary pressures and mechanisms underlying apicomplexan cell division diversification carries relevance across Eukaryota.